Global supply chain : the impact of location variables on competitiveness. - Lim, Lian Kheng. (2010)
Increased globalisation and the need for greater organisational integration has led the argument back to the possibility of achieving competitive advantage through improved supply chain coordination and management. Location, as a factor, is logically an important element which might affect the performance of the entire supply chain. However, this is also one of the least studied element in supply chain management. This research aims to study the possible effects that location variables might have on the performance of the supply chain. An analytical framework connecting location variables with the uncertainties and the performance of the supply chain is presented. This framework is tested through a questionnaire survey based empirical method of investigation.